Ventricular Septal Defect from Takotsubo Syndrome - Lu, Daniel Y. (Case Rep Cardiol, 2016)
Takotsubo Syndrome is a transient condition characterized by left ventricular systolic dysfunction with apical akinesis/dyskinesis and ballooning. Although the prognosis with medical management is excellent in most cases, rare cases of serious complications can occur. We present here a case of a 71-year-old woman presenting with acute decompensated heart failure with initial findings consistent with a myocardial infarction, who was found instead to have an acute ventricular septal defect as a complication of Takotsubo Syndrome.